Rancangan Desain Karakuri dengan Memprioritaskan Kebutuhan Customer Menggunakan Metode Quality Function Deployment (QFD) - Satibi, Ilham; Wiyatno, Tri Ngudi; Supriyati, Supriyati (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This study aims to design a karakuri system that aligns with customer needs using the Quality Function Deployment (QFD) method. The research was conducted at one of PT. Trustindo Mekatronic Mulya’s clients, who required a supporting tool to ease operator workload during the material transfer process. Data was collected through interviews and field observations, then analyzed using the House of Quality to translate customer needs into relevant technical specifications. The results indicate that a manual karakuri mechanism using pipe joint materials is the most suitable solution due to its simplicity, energy efficiency, flexibility, and low cost. This design allows for ergonomic box material movement without relying on external energy sources, thereby enhancing operational efficiency and operator comfort. The findings confirm the effectiveness of the QFD method in producing functional, cost-effective, and user-oriented product designs.